Persistent Down-Beating Torsional Positional Nystagmus: Posterior Semicircular Canal Light Cupula? - Akihide Ichimura; Koji Otsuka (Case Reports in Otolaryngology)
A 16-year-old boy with rotatory positional vertigo and nausea, particularly when lying down, visited our clinic. Initially, we observed vertical/torsional (downward/leftward) nystagmus in the supine position, and it did not diminish. In the sitting position, nystagmus was not provoked. Neurological examinations were normal. We speculated that persistent torsional down-beating nystagmus was caused by the light cupula of the posterior semicircular canal. This case provides novel insights into the light cupula pathophysiology.